2014
DOI: 10.1016/j.jretconser.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Mobile marketing: A literature review on its value for consumers and retailers

Abstract: The article describes the existing knowledge of how mobile marketing can increase value for consumers and retailers. Mobile device shopping, and consumers' use of mobile devices while shopping is shown to be both an extension of consumers' shopping behaviours developed on Internetconnected desktop and laptop computers (PC), and potentially new behaviours based on a mobile devices' uniquely integrated features such as camera, scanners and GPS. The article focuses on how mobile marketing creates value for consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 78 publications
3
117
0
5
Order By: Relevance
“…The literature review conducted within the scope of this study was based on reviews about mobile technologies (Leppäniemi, Sinisalo, & Karjaluoto, 2006;Ngai & Gunasekaran, 2007;Varnali & Toker, 2010;Zhang, Zhu, & Liu, 2012, Ström, Vendel, & Bredican, 2014. Within this context, articles that are analysed by the studies in question were scanned in line with the aims of this study.…”
Section: Mobile Marketing Literature Reviewmentioning
confidence: 99%
“…The literature review conducted within the scope of this study was based on reviews about mobile technologies (Leppäniemi, Sinisalo, & Karjaluoto, 2006;Ngai & Gunasekaran, 2007;Varnali & Toker, 2010;Zhang, Zhu, & Liu, 2012, Ström, Vendel, & Bredican, 2014. Within this context, articles that are analysed by the studies in question were scanned in line with the aims of this study.…”
Section: Mobile Marketing Literature Reviewmentioning
confidence: 99%
“…Initial trials with beacons indicated potential issue of excessive interaction with users which caused their negative reactions and rejection. Unexpected privacy intrusion by an advertiser can be seen as positive if it fits users behavior and provide added value either as benefits or entertainment [36].…”
Section: B Measuring User Experiencementioning
confidence: 99%
“…[17]" found several major attributes of mcommerce apps: content delivery, transaction, location service, and entertainment.…”
Section: E Essential Functions Of Apps For M-commercementioning
confidence: 99%